Clinical outcomes of NBF gel application in managing mucositis associated with xerostomia - György Szabó; Zsolt Németh; Márton Kivovics (SpringerOpen, 2024)
Abstract Background Xerostomia, or dry mouth, can be a temporary or persistent symptom resulting from various factors, such as medication use, therapeutic radiation, chemotherapy, autoimmune conditions (e.g., Sjögren's syndrome), and hormonal imbalances. Xerostomia often leads to associated mucositis, which significantly impacts patients' quality of life. The nano-bio-fusion (NBF) gingival gel, a gel-type functional toothpaste containing vitamins C, E, propolis, and herbal extracts in a nano-emulsion state, has shown potential in accelerating the healing of oral mucosal lesions. Methods A total of 127 patients (102 females, 25 males) with persistent xerostomia were treated from 2018 to 2023. Of these, 32 patients were treated exclusively with NBF Gel, while 95 patients received NBF Gel in combination with other medications, such as pilocarpine. The underlying causes of xerostomia included irradiation and chemotherapy (12 patients), medication (40 patients), hormonal imbalance (28 patients), and Sjögren's syndrome (47 patients). NBF Gel was applied 2-3 times daily to the tongue and oral mucosa. Treatment effectiveness was evaluated through physical examinations and a patient-reported scale ranging from 1 (no improvement) to 10 (complete improvement), focusing on the healing of mucosal lesions rather than saliva production. Results Both treatment groups showed significant improvements in the healing of xerostomia-associated mucositis, particularly in severe cases with visible lesions. Patients treated with NBF Gel reported improved symptoms related to mucosal health, while those who received combination therapy also experienced reduced side effects of pilocarpine due to dose reduction. The most substantial improvements were observed in patients with drug-induced and hormonally-caused xerostomia-related mucositis. No adverse side effects from NBF Gel were reported during the study. Conclusion NBF gingival gel proved to be beneficial in accelerating the healing of mucositis associated with xerostomia, regardless of the underlying cause, including medication use, radiotherapy, chemotherapy, hormonal imbalances, and Sjögren's syndrome. It presents a promising adjunctive treatment to improve mucosal health and quality of life for patients suffering from xerostomia-associated mucositis.